The slave who was slain twice: Causality and the lex Aquilia (Iulian. 86 dig. D. 9,2,51) - Sirks, A (2011)
D. 9,2,51, in which a slave is slain twice and dies, and where Julian considers both assailants equally liable for killing, has been interpreted in the context of causa superveniens. In that case Julian's opinion becomes contradictory. It is argued that the text should be read in the context of the Stoic theories on causality as current among the jurists in the first centuries AD. In these theories there existed no causa superveniens as of the modern causality theory. As such its application is ill at place here. Instead, in applying these Stoic theories Julian's view can be explained as his attributing a causa antecedens to the first assailant, with full imputation of the effect of the subsequent causa principalis to him, and attributing a causa adiuvans to the second assailant, while valuing at the same time the latter not just as a reinforcing cause but also as a causa mortis and a full effective cause. For other jurists the latter evidently went too far. © 2011 Martinus Nijhoff Publishers.